PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN DIKLAT TERHADAP KINERJA GURU SMP MUHAMMADIYAH WONOMULYO KABUPATEN POLEWALI MANDAR PROVINSI SULAWESI BARAT - Zainuddin, Sri Wahyuni (Siddiq Institute, 2023)
This research aims to examine, analyze, and interpret the influence of Leadership, Compensation, and Training on the performance of Junior High School (SMP) teachers in Muhammadiyah Wonomulyo, Polewali Mandar Regency, West Sulawesi Province. This research is of a quantitative descriptive nature. The population and sample consist of 36 teachers. Data collection methods include interviews, questionnaires, and literature reviews. The research data will be analyzed using statistical tools with SPSS 24 software. The results of the study show that:1. Leadership has a positive and significant influence on the performance of SMP Muhammadiyah Wonomulyo teachers in Polewali Mandar Regency, West Sulawesi Province. Generally, leadership styles have a strong influence on improving teacher performance. Teacher performance is crucial for achieving an organization's goals.2. Compensation has a positive and significant influence on the performance of SMP Muhammadiyah Wonomulyo teachers in Polewali Mandar Regency, West Sulawesi Province. Compensation is a factor that strongly supports all teacher activities with full awareness in developing their skills and thoughts to the maximum to support the organization's goals.3. Training has a positive and significant influence on the performance of SMP Muhammadiyah Wonomulyo teachers in Polewali Mandar Regency, West Sulawesi Province. The purpose of providing training is to meet the economic needs of teachers and to increase work productivity in advancing the organization or institution because teachers are motivated to work better to obtain the training that has been determined.